1999
DOI: 10.1111/1467-9507.00097
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Behavioural Adjustment to Temperament, Parenting and Family Characteristics among 5‐Year‐Old Children

Abstract: The objective of this study was to identify specific temperament, parenting, and family variables, and their interactions, which predict problem behaviours and social skills in children. The subjects were 74 5-6 year old children (34 boys, 40 girls). Results showed different combinations of variables predicted each behavioural outcome, and the child's 'goodness of fit' in the home was a strong predictor of externalising behaviour and social skills. An interaction between temperamental inflexibility and punitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
140
1
8

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 223 publications
(156 citation statements)
references
References 33 publications
7
140
1
8
Order By: Relevance
“…In a study by Belsky et al (1998), negative parenting predicted externalizing problems most strongly in 3-year-old boys who were highly temperamentally negative as infants. Results reported by Paterson and Sanson (1999) indicated that in particular the combination of temperamental inflexibility and punitive parenting resulted in the development of externalizing behavior problems in 5-and 6-year-olds. A combination of high negative emotionality, low fearfulness, and high negative maternal control preceded stable high externalizing trajectories in disadvantaged boys followed from age 2 to 6 in the study by Gilliom and Shaw (2004).…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Belsky et al (1998), negative parenting predicted externalizing problems most strongly in 3-year-old boys who were highly temperamentally negative as infants. Results reported by Paterson and Sanson (1999) indicated that in particular the combination of temperamental inflexibility and punitive parenting resulted in the development of externalizing behavior problems in 5-and 6-year-olds. A combination of high negative emotionality, low fearfulness, and high negative maternal control preceded stable high externalizing trajectories in disadvantaged boys followed from age 2 to 6 in the study by Gilliom and Shaw (2004).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies tested the goodness-of-fit hypothesis in the context of the family (Kochanska, 1995;Mangelsdorf, Gunnar, Kestenbaum, Lang, & Andreas, 1990;Patterson & Sanson, 1999; see for reviews: Bates, 1989;Rothbart & Bates, 1998), but only a few investigations into goodness-of-fit in other child care contexts have been conducted (Carey & McDevitt, 1995). Interactions between temperament and day care characteristics may be crucial in understanding differences in the child's well-being and problem behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Gilliom and Shaw (2004) combined their measurements of harsh control techniques and (the absence of) warmth into an overall measure of maternal negative control. Paterson and Sanson (1999) did measure induction and parental warmth in addition to the negative discipline variables of punishment and expectancy of obedience, but only the interaction between temperamental inflexibility and parental punishment accounted for additional variance beyond main effects.…”
mentioning
confidence: 96%